O processo de implantação do curso de licenciatura em Física a distância pela universidade aberta do Brasil na Universidade Federal de Goiás no polo de apoio presencial em Goianésia - GO na visão de seus gestores - ELIAS, Abdalla Antonios Kayed (2011)
This paper presents the model of management degree in Physics Course by Distance Learning Open University of Brazil at the Federal University of Goiás in support pole in Goianésia - GO in view of its managers. The aim of this study is to analyze the conditions deployment and management degree in Physics course by distance learning System UAB in UFG, the pole in Goianésia - GO, from the perspective of their managers, with the intention of contribute to the development of this teaching modality. In this sense it became necessary to establish specific objectives, answer some questions that guided the development of the work, namely: How distance education was formed in UFG? What is your vision and managers on the course by distance? In an attempt to answer these questions and achieve the main objective, we analyzed throughout the paper, the following aspects related to the course, in view of their managers: 1. the implementation of the course; 2. the Educational Project Course, 3 . the administrative management; 4. the academic staff; 5. the learning process; 6. the assessment of learning; 7. the teaching material. The methodology used in this work was a case study with a qualitative approach, considered here for the most appropriate approach to the object. This work is composed of four chapters. The first presents some views on the course by distance and a brief history of the formation process of distance education in Brazil. In the second, we present the methodological procedures and the paths that were traversed to collect and systematize data. The third presents the analysis of interviews and documents and concluding remarks, we put the points and counterpoints of our analysis and present our personal impressions. Believe that this work can contribute to the development of this mode of teaching, and can also serve as a reference for the implementation of other distance learning courses in physics that can be created. The evaluation of the travel experience, from your project and also the expectations of its agents, managers, teachers, students can indicate problems and questions that nurture certain propose possible solutions and actions that can contribute to these new projects.